Transoral endoscopic thyroidectomy vestibular approach performed at the Hospital Central del Estado de Chihuahua - Enríquez-Sánchez, Luis Bernardo (2024)
Objective: To make a comparison between the transoral endoscopic thyroidectomy vestibular approach (TOETVA) and the conventional open approach of thyroidectomies performed at the Hospital Central del Estado de Chihuahua. Materials and methods: A retrospective study was carried out on 10 patients who underwent total or partial thyroidectomies using either an endoscopic technique or conventional open surgery between March 2018 and March 2019. The study included patient demographics (age and body mass index [BMI]), indications for surgery (tumor size by ultrasound), surgical history and comorbidities, surgical time (in hours for both open and endoscopic procedures), number of conversions required, length of hospital stay, histopathological results from intraoperative and definitive biopsies, and immediate and late postoperative complications specific to both procedures. During the TOETVA, the patients were positioned supine under general anesthesia, with the neck in hyperextension. The oral cavity was disinfected with hypochlorite and a horizontal incision of 1.5 to 2.0 cm was made at the frenulum, followed by dissection through the avascular space to the superior thyroid pole. Results: The patients were female, with a mean age of 46 years; 50 % of them underwent open surgery, while the other 50 % underwent endoscopic surgery. The surgical time of the transoral approach averaged 1.2 hours, compared to 1.5 hours for the open approach. A postsurgical complication in the open surgery group included hypocalcemia due parathyroid gland injury. In the endoscopic surgery group, two procedures required conversion to open surgery because both patients experienced intraoperative hemorrhage. Conclusions: The TOETVA procedure is associated with lower frequency of postoperative pain, is safe and has the advantage of not leaving a visible scar. However, further studies with larger samples are recommended to clearly establish the advantages of this procedure.